Dihydrogen Activation with a Neutral, Intermolecular Silicon(IV)‐Amine Frustrated Lewis Pair. Issue 60 (17th August 2022) - Thorwart, Thaddäus; Hartmann, Deborah; Greb, Lutz
Abstract: The heterolytic cleavage of dihydrogen constitutes the hallmark reaction of frustrated Lewis pairs (FLP). While being well‐established for planar Lewis acids, such as boranes or silylium ions, the observation of the primary H2 splitting products with non‐planar Lewis acid FLPs remained elusive. In the present work, we report bis(perfluoro‐ N ‐phenyl‐ ortho ‐amidophenolato)silane and its application in dihydrogen activation to a fully characterized hydridosilicate. The strict design of the Lewis acid, the limited selection of the Lewis base, and the distinct reaction conditions emphasize the narrow tolerance to achieve this fascinating process with a tetrahedral Lewis acid. Abstract : A silicon Lewis superacid with a novel perfluorinated ortho‐ aminophenol ligand is designed and used in FLP type H2 activation, enabling for the first time the formation of an hydridosilicate directly from H2 . The narrow choice of the Lewis base and the reaction conditions emphasize the commonly encountered difficulties in this challenging hallmark FLP reaction.